2001
DOI: 10.1029/2000wr900188
|View full text |Cite
|
Sign up to set email alerts
|

Preconditions for market solution to urban water scarcity: Empirical results from Hyderabad City, India

Abstract: Abstract. Utilizing both primary and secondary information pertaining to the water sector of Hyderabad City, India, this paper (1) evaluates the economics of various technically feasible supply augmentations options; (2) estimates the group-specific water demand and consumption response functions under alternative pricing behaviors; (3) calculates the net willingness to pay (NWTP, considered to be the value of raw water at source) of different user groups as derived from their respective price elasticities; (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Saleth and Dinar's (2001) study in Hyderabad, India found net WTP to be inadequate to justify supply augmentation options. This is probable as WTP depends on how much the respondents can afford.…”
Section: Methodsmentioning
confidence: 99%
“…Saleth and Dinar's (2001) study in Hyderabad, India found net WTP to be inadequate to justify supply augmentation options. This is probable as WTP depends on how much the respondents can afford.…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest a positive, although highly variable, WTP for supply improvements [Brookshire and Whittington, 1993;Briscoe et al, 1993;Saleth and Dinar, 2001] with some evidence that values were higher for groups enduring lower initial (''baseline'') levels of supply [Altaf et al, 1992]. The magnitude of estimated WTP can be substantial, reflecting the value of the resource under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The low level of social optimum resulting from services ensured by the public utility has led the urban and peri-urban communities to develop alternative strategies based on private groundwater augmentation. These alternative strategies might include direct use of groundwater from a private tubewell, development of a private small supply network fed with untreated groundwater, or supply by tanker, groundwater remaining the primary source of raw water in most of those private supply chains (Ramachandran, 2008;Maria, 2004;Llorente and Zérah, 2003;Saleth & Dinar, 2001). …”
Section: Introductionmentioning
confidence: 99%